On Predicting Voiceless Vowels in Comanche - Armagost, James L. (Kansas Working Papers in Linguistics, 1985)
Comanche voiceless vowels have been analyzed by some authors as phonemic, by others as predictable. This paper reviews the controversy and concludes that voiceless vowels are largely, but not entirely, predictable. Included are several types of data that have received no mention in previous works.